2010
DOI: 10.1017/s0007114509993801
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotic and conventional yoghurt on lipid profile in women

Abstract: Many studies have been done on the hypocholesterolaemic effect of probiotic yoghurt. The results, however, are not conclusive. The aim of the present study was to test the effect of probiotic and conventional yoghurt on the lipid profile in women. In a randomised trial, ninety female volunteers aged 19-49 years were assigned to three groups. Subjects consumed daily 300 g probiotic yoghurt containing Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12 or 300 g conventional yoghurt or no yoghurt for 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(105 citation statements)
references
References 31 publications
4
87
0
14
Order By: Relevance
“…Specific bacterial taxa have been determined to improve lipid markers in the host. Bifidobacteria, which showed positive associations with plasma HDL cholesterol in our previous study (15), have been identified to alleviate dyslipidemia and high-fat-induced insulin resistance when administered as probiotics (46)(47)(48)(49)(50). In addition, some changes in gut microbiota composition induced through host factors might still have pathological consequences, as shown recently for a fat-induced pathobiont expansion caused by changes in the bile acid pool (38).…”
Section: Figmentioning
confidence: 53%
“…Specific bacterial taxa have been determined to improve lipid markers in the host. Bifidobacteria, which showed positive associations with plasma HDL cholesterol in our previous study (15), have been identified to alleviate dyslipidemia and high-fat-induced insulin resistance when administered as probiotics (46)(47)(48)(49)(50). In addition, some changes in gut microbiota composition induced through host factors might still have pathological consequences, as shown recently for a fat-induced pathobiont expansion caused by changes in the bile acid pool (38).…”
Section: Figmentioning
confidence: 53%
“…One of the possible mechanisms by which this effect occurs is through the impact of probiotics on changing intestinal microbiota [8,43]. Probiotic consumption can balance intestinal microbiota for people with T2DM, which might have been caused by the short-chain fatty acids (SCFA) produced from probiotic consumption [44]. Probiotics were effective in suppressing the progression of streptozotocin-induced diabetes [42], in that streptozotocin has the ability to selectively kill pancreatic β-cells, which can decrease endogenous insulin release and increase glucose intolerance [45].…”
Section: Discussionmentioning
confidence: 99%
“…Yoğurt feeding was associated with a clinically relevant decrease in stool frequency and duration of diarrhea in children who have reducing sugars in stools [24]. Positive changes in lipid profile were observed in both yoğurt groups [25].…”
Section: A Cultural Product Related To Probiotics: Yogurt (Yoğurt)mentioning
confidence: 88%